2005
DOI: 10.1536/ihj.46.795
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive Protein Is Related to Impaired Oxygenation in Patients With Acute Aortic Dissection

Abstract: SUMMARYImpaired oxygenation sometimes occurs in patients with acute aortic dissection, however, the mechanism has not been fully investigated. We hypothesized that impaired oxygenation is related to inflammation secondary due to aortic dissection. Patients with acute aortic dissection who had received 14 days of conservative treatment were retrospectively examined. Patients who had undergone surgery or died within 14 days were excluded. Patients who had evidence of having pneumonia or pulmonary congestion duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 13 publications
4
37
0
Order By: Relevance
“…The incidence of presurgical mild ARDS in this series was similar to other series which reported the incidence of 30-45%, [1][2][3][4][5] and this study showed that patients in the mild-ARDS group, compared with the no-ARDS group, had significantly higher plasma levels of inflammatory marker, C-reactive protein, which was consistent with the findings of previous studies. [17][18][19] So, this study again suggested that systemic inflammation played an important role in the occurrence and development of mild ARDS.…”
Section: Discussionsupporting
confidence: 59%
“…The incidence of presurgical mild ARDS in this series was similar to other series which reported the incidence of 30-45%, [1][2][3][4][5] and this study showed that patients in the mild-ARDS group, compared with the no-ARDS group, had significantly higher plasma levels of inflammatory marker, C-reactive protein, which was consistent with the findings of previous studies. [17][18][19] So, this study again suggested that systemic inflammation played an important role in the occurrence and development of mild ARDS.…”
Section: Discussionsupporting
confidence: 59%
“…CRP was reportedly normal at admission in most AAD patients (19,20). Therefore, it is likely that the elevation of admission CRP was not caused by AAD but by other forms of chronic inflammation which existed before the onset of AAD.…”
Section: Discussionmentioning
confidence: 94%
“…Maximal CRP was only predicting the impaired oxygenation, but not Stanford type, thrombosed false lumen, pleural effusion, atelectasis, and intravenous vasodilator use. At admission, CRP was normal and increased significantly since day 2 in the impaired oxygenation group [48]. Increased admission CRP correlated with high mortality irrespective of management policy [49].…”
Section: D-dimer and Aortic Diseasesmentioning
confidence: 89%